2017
DOI: 10.1590/1678-4162-9005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed intake containing whole cottonseed on blood parameters of Nellore bulls

Abstract: The aim of this study was to evaluate the effect of diets containing whole cottonseed (WC) on blood biochemical parameters of bulls. Thirty bulls with 30±6 months and 382.7±28.4kg were kept in feedlot (85 days) and fed the following WC levels: 0, 2. 22, 4.44, 6.66, 8.88

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that the moisture content during extrusion helps the destruction of some aflatoxins, in addition to a high moisture concentration in the extruded product increases the loss of toxic factors [6]. According to Gomes et al [4], cotton flour contains 0.1-0.4% free gossypol. The processing of cotton flour, especially at high temperatures, favors the reduction of gossypol and it has been suggested that diets containing up to 200 mg of free gossypol are safe for ruminants, while 400 mg is the limit for considering it toxic, and, at levels greater than 800 mg, causes death [4].…”
Section: Gossypolmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the moisture content during extrusion helps the destruction of some aflatoxins, in addition to a high moisture concentration in the extruded product increases the loss of toxic factors [6]. According to Gomes et al [4], cotton flour contains 0.1-0.4% free gossypol. The processing of cotton flour, especially at high temperatures, favors the reduction of gossypol and it has been suggested that diets containing up to 200 mg of free gossypol are safe for ruminants, while 400 mg is the limit for considering it toxic, and, at levels greater than 800 mg, causes death [4].…”
Section: Gossypolmentioning
confidence: 99%
“…According to Gomes et al [4], cotton flour contains 0.1-0.4% free gossypol. The processing of cotton flour, especially at high temperatures, favors the reduction of gossypol and it has been suggested that diets containing up to 200 mg of free gossypol are safe for ruminants, while 400 mg is the limit for considering it toxic, and, at levels greater than 800 mg, causes death [4].…”
Section: Gossypolmentioning
confidence: 99%
See 1 more Smart Citation